FORMS AND METHODS OF APPLYING SIBELIUS, AURALIA, STEINBERG CUBASE PROGRAMS IN IMPROVING TEACHING METHODOLOGY IN MUSIC EDUCATION - Akhrorov Khurshid Khamidovich (Journal of Learning on History and Social Sciences, 2024)
This article describes the forms and methods of using Sibelius, Auralia, Steinberg Kubase programs in improving the teaching methodology in music education. Also, using the possibilities of these programs, the ways to improve the quality of lessons are shown and necessary recommendations are given